Analysis of Determinants on Village Fund Management Accountability - Dias Widiawati; Nur Laila Yuliani; Anissa Hakim Purwantini (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Village fund management accountability is the most important focal point for village officials because it shows responsibility and success in managing village funds. Accountability is an important part in providing reports and being accountable for any success or failure in carrying out the goals that have been set by the organization previously. Factors that influence the success of village fund management accountability are village apparatus competence, control system, use of technology, community participation, village financial system and transparency.This study aims to empirically test and analyze the effect of village apparatus competence, internal control system, technology utilization, community participation, village financial system and transparency on village fund management accountability in villages in Candimulyo District. The sample of this study amounted to 108 respondents, where the sampling technique in this study used purposive sampling. The data collection method used is a questionnaire. The hypothesis testing technique in this study uses multiple linear regression analysis, F-test and t-test. Based on the tests that have been carried out, the results of the study show that the competence of the village apparatus has a positive effect on the accountability of village fund management. Based on this research, the internal control system, the use of information technology, community participation, the village financial system and transparency have no effect on the accountability of village fund management.